Investigation of enzyme reaction by surface plasmon resonance (SPR) technique - Wangkam T. (2014)
An investigation into the surface plasmon resonance (SPR) sensor surface for the detection of enzyme reaction is reported. The thin polymeric film is prepared by spin casting poly (styrene-co-maleic acid) [PSMA] on a chromium/gold-coated SPR substrate. Bovine serum albumin (BSA) is adsorbed onto this surface with a mix of side-on and end-on orientation. The adsorbed BSA was tested against the protease where the cleavage reaction was followed by the change in the resonance angle of the SPR. The kinetic of the enzyme reaction follows the Michaelis-Menten equation where the reaction depends on the concentration of protease. The protease concentration is in the range of 2.5 μg/ml to 1.25 mg/ml. The different topology of protein surface before and after enzyme cleavage was observed by atomic force microscope (AFM). The AFM result shows uncleaved BSA on the surface even at highest protease concentrations owing to the steric hindrance of the adsorbed protease on the BSA surface. The sensor surface can be cleaned by cleaning solution and the surface can be reused, which avoids repetition of the complicated preparing of the sensor surface. © 2009 Elsevier B.V. All rights reserved.